Patch testing in hand eczema: a cross-sectional study from a teaching hospital of North India - Qayoom, Seema; Rather, Suhail R.; Khan, Kafeel (International Journal of Research in Medical Sciences, 2018)
Background: Hand eczema is a common dermatological disorder in different occupational groups with multifactorial etiology. Patch Testing serves as an important tool for identifying responsible allergens. Methods: The study was conducted in the Department of Dermatology, SKIMS-MCH, Srinagar for duration of one year from June 2016 to June 2017. Patients of either gender with hand eczema, aged 18 years and above, presenting to outpatient department were enrolled in the study. After taking informed written consent from patients, a detailed history was taken, and clinical examination was performed on first visit. Patch testing with Indian Standard Series was performed a fortnight after complete resolution of signs and symptoms of eczema and after complete withdrawal of the drugs. Results: Out of 116 patients 60 (51.7%) were males and 56 (48.3%) were females. Male to female ratio was 1.07:1. Mean age of presentation of females was 35.42±12.52years and of males was 49.2±10.01years. The commonest allergen was Nickel sulphate (23.2%) followed by Potassium dichromate (15.1%). Nickel sulphate was most common allergen in females while Cobalt sulphate and Paraphenylene diamine were most common allergens in males. House wives (36.2%) and farmers (11.2%) were occupations with high frequency of hand eczema. Conclusions: Patch testing in clinically diagnosed cases of hand eczema can play a vital role in not just the confirmation of the label but can also reduce the socio-economic burden on such patients.